Preparedness of healthcare professionals towards a new crisis: a short review of experiences, challenges, and lessons from the covid-19 pandemic - Konstantinidis, Kleanthis; Apostolakis, Ioannis (Health & Research Journal, 2023)
Background: The healthcare professionals have had to adapt their current practices and implement new strategies, to ensure a safe patient care environment during the COVID-19 pandemic. In addition, their training in the new conditions of the pandemic has been challenging. Aim: The aim of this short review is to provide a brief record of the experiences and challenges faced by healthcare professionals and how these can constitute lessons for a new health crisis. Method and Material: We conducted literature research in two electronic databases for the period from 2020 to 2022, using keywords. The collected material was classified based on the objectives set. A selection of literature sources was made, followed by a review with the creation of note cards. Results: The review of the selected sources reveals challenges in the practice of healthcare professionals, the continuation of professional development and research activities, as well as the adoption of digital technologies and tools for communication, information and training. The lack of experience of healthcare professionals from a previous pandemic crisis and the delay in the digital transformation of healthcare are some of the obstacles, which can become lessons for the preparedness of the healthcare systems towards a new health crisis. Conclusions: The findings highlight the essential role of a well-trained and well-informed healthcare workforce, to adequately face a health crisis. The analysis of these findings can contribute to the detection and identification of emerging needs of healthcare professionals, allowing policymakers to implement effective interventions for the continuing development of the workforce.